Characteristics of the Electrical Conductivity of the Basalt-Aluminum System Manufactured by Powder Technology (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
This study included reinforcement of basalt powders with aluminum using powder method, where the reinforcement ratios of aluminum were (0, 10, 20. 30, 40 and 50%) with basalt material as a matrix. The two powders were mixed and have been pressed up to (4 ton) for (1 minute). The samples were sintered inside an oven at a temperature of (1000 ˚C) with the presence of Argon (Ar) gas in order to minimize oxidation, along two hours. The microscopic structure of the samples has been examined using scanning electron microscope (SEM)  along with the electrical properties in the frequency range between (50-5×106 Hz). The electrical properties included (real and imaginary dielectric constant, loss angle, electrical conductivity, electrical resistivity) were studied with the ranged frequencies at room temperature. The microstructure properties exhibited a homogenized properties especially sample with (20%Al). Concerning the electrical properties, the results showed a decrease in the dielectric constant and the loss angle with increasing the frequency and increasing the conductivity values at the (20%Al)  among other samples.